Perception of dairy farmers about Gangatiri cattle rearing in eastern Uttar Pradesh - Singh, Puspendra Kumar; Sankhala, Gopal; Singh, P K (Indian Journal of Dairy Science, 2018)
Present study was undertaken in the native tract of Gangatiri breed of cattle with 108 dairy farmers of eastern Uttar Pradesh, who were rearing these cattle for their livelihood security. Paper deals with Socio- personal and socio- economic study as well as feedback of dairy farmers about Gangatiri cattle rearing. More than half of respondents were in middle age group and had cattle rearing as a main occupation. These cattle were reared mostly (42.59%) by marginal farmers, having small herd size with most (46.30%) of respondents and 39% of the respondents had low mass media exposure. However, Gangatiri cattle rearing share more than half (56.73 %) of total annual income of these respondents, showing importance of rearing these cattle. About 87.96 % of respondents were perceived that Gangatiri cattle are suitable to rear under local climatic condition, while 81.48% respondents were agreed about successfully management of Gangatiri cattle during extreme weather conditions with easily and locally available prevention methods. Around 86.00% respondents were perceived that a lot of time was needed for grazing this cattle and it is the main managerial problem. It can be conclude that Gangatiri cattle rearing has important contribution to livelihood of respondents and efforts like making availability dairy infrastructure, conservational and promotional schemes for rearing this breed, strengthening of milk marketing infrastructure in area will not only help in improvement of reproductive and productive performance of these cattle but also help these farmers to realize better profit from rearing these cattle.